Efektivitas Pelayanan Izin Usaha Perdagangan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Manado - Pratiwi, Deswina Dede; Rorong, Arie Junus; Ruru, Joorie Marhaen (Sam Ratulangi University, 2017)
ABSTRACT : This study aims to explain the effectiveness of trade license business services at the One Stop Investment and One Step Service (DPMPTSP) at Manado City in order to improve public service to the public. The licensing service is implemented by DPMPTSP of Manado City based on Mayor Manado Regulation No. 4 year 2017 on licensing and non licensing in DPMPTSP Manado City. This research uses descriptive method of qualitative approach with data collection technique which is done by observation, interview, and documentation technique. Number of informants as many as 9 people. In this research, we use the effectiveness measurement in terms of process approach according to Lubis and Huseini, which in this approach include 5 indicators as follows: (i) service efficiency, (ii) service procedure, (iii) employee responsiveness, (iv) coordination between leader and subordinate, (v) infrastructure facilities. The result of the research shows that the trade license business serivice in DPMPTSP of Manado City has not been maximal or not yet effective, it can be seen on the settlement of inappropriate trade business license, inadequate work space infrastructure, lack of technical team resulting in more work load, injustice or still distinguish one another where employees are more concerned with the friendship in providing services.Key words: Effectiveness, Service, Trade License Business